Clinical Mastitis Incidence in Dairy Cows Housed on Recycled Manure Solids Bedding: A Canadian Cohort Study - Fréchette, Annie; Fecteau, Gilles; Côté, Caroline; Dufour, Simon (Frontiers in Veterinary Science, 2021)
Bedding can affect mammary health of dairy cows. The objectives of this study were to evaluate clinical mastitis incidence in cows housed on recycled manure solids bedding and, more specifically, to determine which pathogens were involved. We followed 26 recycled manure solids farms and 60 straw-bedded farms as a comparative group during one year (2018-2019). For each episode of clinical mastitis, defined as a visual alteration of the milk, with or without local or systemic signs of infection, producers sampled aseptically the affected quarter, provided some details about the animal, and sent the sample to the research team at the Université de Montréal. We received and analyzed 1,144 milk samples. The samples were cultured according to the National Mastitis Council guidelines and the different colonies phenotypes were subsequently identified with mass spectrometry. In 54.6% of CM cases, a single phenotype of bacteria was cultured (pure culture) while two different phenotypes were found in 16.8% of the samples (mixed culture), and no growth was observed in 14.4% of the samples. Samples with three or more phenotypes were considered contaminated and where not included in the pathogen-specific analyses (14.3% of the submitted samples). The most frequently identified bacterial species in pure and mixed culture in farms using recycled manure solids were Streptococcus uberis (16.0%), Escherichia coli (13.8%), Klebsiella pneumoniae (13.2%), Streptococcus dysgalactiae (6.2%) and Staphylococcus aureus (3.4%). In straw farms, the most frequent species were Staphylococcus aureus (16.6%), Streptococcus uberis (11.0%), Escherichia coli (9.1%), Streptococcus dysgalactiae (8.0%) and Klebsiella pneumoniae (1.1%). Incidence of clinical mastitis (all cases together) was not higher in recycled manure solids farms (14.0 cases/100 cow-year; 95%CI: 8.3-23.7) compared to straw-bedded farms (16.3 cases/100 cow-year; 95%CI: 9.0-29.6). However, Klebsiella pneumoniae clinical mastitis episodes were 7.0 (95%CI: 2.0-24.6) times more frequent in recycled manure solids farms than in straw farms. Adjusted least square means estimates were 1.6 Klebsiella pneumoniae clinical mastitis cases/100 cow-year (95%CI: 0.8-3.4) in recycled manure solids farms versus 0.2 cases/100 cow-year (95%CI: 0.1-0.6) in straw-bedded farms. Klebsiella pneumoniae clinical mastitis are in general severe. Producers interested in this bedding alternative need to be aware of this risk.